How the Structural elucidation of the natural product Stephanosporin led to new developments in aryl radical and medicinal chemistry - Fehler, Stefanie; Heinrich, Markus (Synlett, 2015)
The intent of this account is to provide a focused overview of recent developments in aryl radical chemistry, especially extensions and applications of the Meerwein arylation and the Gomberg-Bachmann reaction. Although most of the reactions and methods described were discovered on the basis of earlier findings made by our group or logically depend on newly discovered reactivities or mechanistic principles, the rapid evolution of radical chemistry can nevertheless be traced back to the behavior of the natural product stephanosporin, which is capable of liberating 2-chloro-4-nitrophenol via an aryl radical intermediate.
Keywords: arylations; diazonium compounds; Gomberg-Bachmann reactions; hydrazines; Meerwein reactions; radical reactions